Technical Assessment and Engineering Analysis of a Horizontal Sterilizer Pressure Vessel for Palm Oil Processing: Case Study of a 14-Ton Capacity System - Bimo Arif Syahputra; Irwansyah Irwansyah (MSD Institute, 2025)
Palm oil processing represents a vital industry in Indonesia, which exported over 36 million tons of palm oil products in 2019. Sterilization is a critical process in palm oil extraction that directly impacts product quality and processing efficiency. This study presents a comprehensive engineering analysis and design specification for a horizontal sterilizer pressure vessel with a 14-ton capacity used in palm oil processing. Using a rational design methodology, we documented and analyzed the specifications of a sterilizer system operating at pressures of 2.8-3.0 kg/cm² and temperatures of 135-140°C. The research includes detailed calculations of vessel dimensions, wall thickness requirements, and volume characteristics. Results yielded comprehensive specifications including a vessel length of 21.5 m, diameter of 3 m, wall thickness of 15 mm, and total volume of 151.9 m³. These parameters establish a complete engineering basis for sterilizer design, fabrication, and maintenance. The study contributes to the limited scholarly literature on palm oil processing equipment design and provides valuable reference material for engineers developing similar systems. This documentation of industrial knowledge bridges the gap between theoretical pressure vessel design and practical applications in the palm oil industry.